Securing land and water for food production through sustainable land reform: a nexus planning perspective - Nhamo, L.; Mpandeli, S.; Liphadzi, S.; Mabhaudhi, Tafadzwanashe (MDPI, 2022)
Land and water are vital resources for sustaining rural livelihoods and are critical for rural development as they form the basis of agriculture, the main economic activity for rural communities. Nevertheless, in most developing countries, land and water resources are unevenly distributed due to historical and socio-economic imbalances, hence the need for land reform policies to address these disparities. However, redistributing land without considering the interconnectedness of land and socio-ecological systems can compound existing food and water insecurity challenges. This study used a mixed research method, integrating both quantitative and qualitative data, to develop a framework to guide policy and decision-makers to formulate coherent strategies towards sustainable land redistribution programmes and achieve the desired outcomes. The approach was vital for integrating the broad and intricate interlinkages between water, land, and environmental resources. Therefore, the framework is based on transformative and circular models for informing strategic policy decisions towards sustainable land redistribution. The focus was on South Africa’s land redistribution plans and the implications on water and food security and rural development. The developed framework is designed to ensure the sustainability of agrarian reform and rural economic development. It is framed to address land and water accessibility inequalities, promote water and food security, and enhance rural development. A sustainable land redistribution increases the adaptive capacity of rural communities to climate change, enhances their resilience, and provides pathways towards Sustainable Development Goals (SDGs).